Pelestarian Padi Lokal Sambay Simeulue Aceh melalui Sosialisasi, Konservasi, Peningkatan Varietas, dan Rekayasa Genetik - Efendi, Efendi; Muyassir, Muyassir; Helmi, Helmi; Zulwanis, Zulwanis; Hidayat, Taufan (Universitas Syiah Kuala, 2023)
Abstract: The province of Aceh has a wealth of local varieties, such as Aceh's local rice, which comes in various types and plays a crucial role in human life. Therefore, it needs to be managed and utilized in a sustainable, harmonious, and balanced manner for the greatest prosperity of the people. The conservation and utilization of the Aceh Sambay Simeulue local rice germplasm have been successfully carried out through systematic field surveys, coordination with the government, and community outreach. The tested Sambay Simeulue rice has yielded 20 pure lines in the early generation. Socialization, conservation, and rice breeding activities have produced candidates for new superior varieties, which have been implemented on Simeulue Island. The new superior rice lines resulting from the selection process exhibit promising characteristics, including productivity reaching 8 tons/ha and excellent rice taste. As a result, the utilization of Sambay Simeulue superior rice has been enhanced by increasing support for the supply of superior varieties through partnerships. Additionally, efforts have been made to strengthen seed institutions for large-scale production. By optimizing seed production on a wider scale, the use of quality seeds from superior varieties, produced through community service, can be further increased.